Short reflections on the history of African communication - Bussotti, L. (Historia y Comunicación Social, 2015)
This article aims to propose a chronological subdivision in the history of African communication. African communication today is one of the most important axes for implementing development strategies, sustaining education, health, and schooling programmes, and so on. However, many of these programmes fail due to a lack of or ineffective communication between international organisations, local elite and lay people. The reasons for this situation must be found in Africa's history of communication, which has undergone radical transformations in its different phases. Using the functionalist analysis drawn up by Jakobson, this article proposes a new chronological subdivision of Africa's history of communication, reflecting on the current contradictions in contemporary communication in Africa.